Analysis of the Situation of Cooperative Bank Groups in Poland in a Changing Macroeconomic Environment - Folwarski, Mateusz (Journal of Finance and Financial Law, 2023)
The purpose of the article/hypothesis. Cooperative banks in Poland face numerous challenges – both related to the current problems of the entire banking sector and the issue of concentration of the cooperative system. Current challenges of the banking sector in Poland – especially systemic ones, as well as the unstable macroeconomic environment make it difficult for cooperative banks to compete with the commercial banking sector and the FinTech and BigTech sectors. In addition, the ongoing processes of digitalization of the banking market are challenging cooperative banks in terms of the direction of their further development – the commonality of services and concentration of banks, or maintaining the current structure of cooperative banks in Poland. The research hypothesis of the article was that cooperative banks are able to maintain a high level of stability and efficiency despite the unstable macroeconomic environment.Methodology. The main objective of the research was to analyze individual groups of cooperative banks in Poland in 2020–2023 in terms of adaptation to the changing macroeconomic environment, which has been particularly difficult in the recent period in terms of planning and implementation of strategic objectives. The study analyzed more than 300 cooperative banks belonging to the BPS group, which were divided into five groups taking into account the criterion of balance sheet total (banks over 1 billion PLN, 500–1 million PLN, 200–500 million PLN, 100–200 million PLN, and banks with a balance sheet total of less than 100 million PLN). Groups of cooperative banks were analyzed on the basis of scoring criteria in terms of indicators: capital adequacy, asset quality, efficiency, liquidity – on a quarterly basis.Results of the research. The study showed that the group of small cooperative banks performed significantly better in an unstable macroeconomic environment – especially during the COVID pandemic – 19. Despite this, in an unstable macroeconomic environment especially in an environment of relatively low interest rates (in 2020–2021), the discussion regarding concentration processes as well as commonality of banking services in the cooperative sector intensified. However, in a still unstable macroeconomic environment, but in an environment of relatively high interest rates (in 2022–2023), cooperative banks belonging to large, medium and smaller banking groups have significantly improved indicators of capital adequacy, asset quality, efficiency, liquidity – often demonstrating a much more effective management of a smaller institution than large cooperative banks – very often resulting from the local nature of their operations. Therefore, an important aspect of the functioning of the cooperative sector in Poland may be issues of commonality of financial services and products, rather than processes of sector consolidation. In the literature, the cooperative sector shows a willingness to commoditize especially bank reporting, marketing activities and the implementation of new technological solutions. An important challenge for the cooperative sector may be the response of small cooperative banks to falling interest rates.